Ciprofloxacin Increased Cytotoxicity of Normal Bone Marrow Stem Cells in Mice Treated With Cyclophosphamide and Etoposide - Suhool Kareem (Journal of Global Pharma Technology, 2018)
The effects of ciprofloxacin (Cipx) on the cytotoxicity of cyclophosphamide (CP), etoposide (VP-16), and combinations thereof on normal bone marrow stem cells in mice were studied. Cipx was administered prior to or after treatment with CP and VP-16. Chromosomal aberration (CA), micronucleus (MN) and mitotic index (MI) were used as markers. CP, VP-16 and Cipx and their combinations were injected intraperitoneally at concentrations of 2, 20, 9.5 mg/kg, respectively. Control groups were injected with normal saline and DMSO solution. Cytogenetic analyses were carried out after 24 hrs of treatment. CP and VP-16 reduced MI and increased CA and MN; while Cipx did not produce significant cytotoxic effects when used alone. Additional cytotoxic effects were seen when Cipx was injected before CP and VP-16 combination. Highest effect was observed when Cipx was injected after injecting combination of CP and VP-16 (p≤0.05).In conclusion; Cipx increased the cytotoxic effects of CP and VP-16 when used before and after treatments with combinations of CP and VP-16.Keywords: Cyclophosphamide; Etoposide; Ciprofloxacin; bone marrow; chromosomal aberration; micronucleus; Mitotic index; cytotoxicity.